2021
DOI: 10.1177/08912424211036180
|View full text |Cite
|
Sign up to set email alerts
|

Big Tech on the Block: Examining the Impact of Tech Campuses on Local Housing Markets in the San Francisco Bay Area

Abstract: The rapid growth of tech company headquarters such as Apple, Facebook, and Google could potentially put new pressure on the housing market in adjacent residential neighborhoods, in the form of housing price appreciation and real estate speculation. This article examines the relationship between the big tech corporate campuses and Silicon Valley/San Francisco housing markets using the Zillow (ZTRAX) transaction and tax assessor data. The authors compare real estate activity adjacent to new company locations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although few studies have examined the determinants of Fintech and Bigtech credit (Arslanian and Fischer, 2019;Menat, 2016), no studies have examined the macro-financial determinants of Fintech and Bigtech lending. This study is different from prior studies that provide case studies about how specific Fintech or Bigtech credit products improve access to finance (Balyuk et al, 2020;Chapple and Jeon, 2021). This study is also different from other studies that focus on the disruption caused by Fintech and Bigtech players (Vives, 2019).…”
Section: Introductionmentioning
confidence: 70%
“…Although few studies have examined the determinants of Fintech and Bigtech credit (Arslanian and Fischer, 2019;Menat, 2016), no studies have examined the macro-financial determinants of Fintech and Bigtech lending. This study is different from prior studies that provide case studies about how specific Fintech or Bigtech credit products improve access to finance (Balyuk et al, 2020;Chapple and Jeon, 2021). This study is also different from other studies that focus on the disruption caused by Fintech and Bigtech players (Vives, 2019).…”
Section: Introductionmentioning
confidence: 70%
“…They found the opposite was significant with Walmart stores increasing housing prices by 2% to 3% for houses located within 0.5 miles of the store and by 1% to 2% for houses located between 0.5 and 1 mile. Chapple and Jeon (2021) investigated the relationship between the big tech corporate campuses and Silicon Valley housing markets using the Zillow transaction and tax assessor data. They revealed that housing prices near the tech campus increased by 7%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They could develop retraining programs to help workers with low levels of formal education and upgrade skills for the new jobs created by OFDIs. City-regions may also want to consider how firms' OFDI activities relate to corporate expansion processes and potentially put pressure on housing markets (Chapple and Jeon, 2021). What is important to note here is that these city-regions are not only in vital need for specific policy interventions; but because of successful OFDI activity and ongoing international engagement, they also benefit from high tax revenues and are, thus, in a position to actively engage in the public policies needed to reduce income polarization.…”
Section: Cr 333mentioning
confidence: 99%